The New Public Management Towards a Strategic Approach to Management Control : Case of Public Establishments and Enterprises in Morocco - AHADI , Hajar; BENABDELHADI , Abdelhay (Revue Internationale des Sciences de Gestion, 2024)
The public and private sectors have both the two insiders of the modernizing reforms to meet the pressing needs of citizens and align the economic and social infrastructure of the country with the environmental changes. The Moroccan state has integrated the principles of New Public Management to optimize the management of the public property, and to establish management methods focused on the value creation. This article explores the contribution of the New Public Management to the evolution of management control to a strategic lever, which exceeds its strictly financial dimension, to improve the overall performance of the Public establishments and enterprises in Morocco. By analyzing the effects of these reforms, we show how a results-focused approach can transform administrative practices, strengthen governance within public institutions and increase citizen satisfaction. This approach makes it possible to establish clear performance indicators, hold public managers accountable and encourage innovation in administrative processes.